Beamforming Techniques for Smart Antenna using Rectangular Array Structure - S.K. Bodhe; B.G. Hogade; Shailesh Dharma Nandgaonkar (Institute of Advanced Engineering and Science, 2014)
In this paper, array theory in general has been discussed. Basic fundamentals of smart antenna and beamforming techniques using rectangular array theory is discussed. Two techniques, Matrix inversion and IDFT method , for their pros and cons were described which were used for beamforming. Both the techniques found to be useful as their areas of application differs on hardware background. The design of a fully spatial signal processor using rectangular array configuration is presented in this paper. It has wideband properties and,hence eliminates the requirement of different antenna spacing. Furthermore,frequency selectivity and rejecting unwanted signals gives the satisfactory performance for practical implementation.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5860